An Empirical Assessment of the Role of Organizational Citizenship Behavior in Explaining Academic Success: Some Evidence from East Malaysian Sample - Magdalene Ang Chooi Hwa; T Ramayah (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
Management researchers have consistently reported the significant role of organizational citizenship behavior (OCB) in predicting individual success in organizational settings. This topic, however, has been largely ignored in the business education environment. Given the demonstrable benefits of OCB enactment in terms of influencing performance evaluations and organizational rewards, we emphasize the importance of examining the role of OCB in predicting student performance and their eventual career success. This endeavor holds important implications for students who are on the threshold of entering the industry. Using a self-administered questionnaire, we collected data from a total of 177 undergraduate students from two different schools in a Malaysian public university. Analysis reveals that of the three distinct dimensions of OCB, only one (consisting of altruism and courtesy items) has influences on both measures of student performance (i.e., productivity and cumulative grade point average). Implications of these findings are discussed.